2011
DOI: 10.1371/journal.pone.0017550
|View full text |Cite
|
Sign up to set email alerts
|

Location of Intra- and Extracellular M. tuberculosis Populations in Lungs of Mice and Guinea Pigs during Disease Progression and after Drug Treatment

Abstract: The lengthy treatment regimen for tuberculosis is necessary to eradicate a small sub-population of M. tuberculosis that persists in certain host locations under drug pressure. Limited information is available on persisting bacilli and their location within the lung during disease progression and after drug treatment. Here we provide a comprehensive histopathological and microscopic evaluation to elucidate the location of bacterial populations in animal models for TB drug development.To detect bacilli in tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
118
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 80 publications
(127 reference statements)
7
118
0
Order By: Relevance
“…The hypoxic nature of necrotic TB granulomas has been reported in other animal models for tuberculosis infection, such as guinea pigs, rabbits, and nonhuman primates (23,62), but is generally not observed in the mouse model of infection (45). We evaluated oxygen tension in the late stage of the Kramnik model using immunohistochemical detection of pimonidazole hydrochloride (Hypoxyprobe) adducts throughout the progression of disease.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The hypoxic nature of necrotic TB granulomas has been reported in other animal models for tuberculosis infection, such as guinea pigs, rabbits, and nonhuman primates (23,62), but is generally not observed in the mouse model of infection (45). We evaluated oxygen tension in the late stage of the Kramnik model using immunohistochemical detection of pimonidazole hydrochloride (Hypoxyprobe) adducts throughout the progression of disease.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, encapsulation of lesions by fibrous connective tissue may represent a physical barrier to drug penetration, which was recently indicated in a study using the rabbit model (49). We have shown in animal models that develop necrotic lesions that the majority of bacilli are extracellular and admixed with debris from necrotic host cells (23). Because these lesions more closely mimic what occurs in humans with naturally occurring TB, it is desirable to evaluate any promising new TB drug regimen under similar, clinically relevant in vivo conditions.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…It was previously believed that Mtb were sparse in the caseum, based on Ziehl-Neelsen acid-fast staining, with most of the detectable bacilli persisting at the periphery. 126 A recently developed acid-fast technique using Auramine O and Rhodamine B revealed that the majority of bacilli are actually in the necrotic core in guinea pig caseous granulomas, 102 but the viability of these bacilli remains unclear. Mtb adapt to this environment by preferentially using fatty acids in their metabolism, slowing down active replication, and increasing cell wall thickness, entering a so-called dormant state.…”
Section: Pathogenesis and Lesion Developmentmentioning
confidence: 99%
“…In addition, the bacilli within human pulmonary granulomas, especially those involved in cavitary disease and transmission, are believed to be primarily extracellular (19). However, the bacilli within the lungs of traditional mouse models of infection are predominantly intracellular (20). Therefore, the efficacy of compounds that preferentially accumulate within macrophages could be overestimated by testing in an animal model that lacks necrotic lesions containing abundant extracellular bacilli.…”
mentioning
confidence: 99%